The prevalence of sleep breathing disorders in patients with atrial fibrillation undergoing catheter treatment - M. V. Agaltsov; O. M. Drapkina; K. V. Davtyan; G. G. Arutyunyan (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To study the prevalence of obstructive sleep apnea (OSA) among patients with atrial fibrillation (AF) who have undergone catheter treatment for this arrhythmia, as well as to study the possible interrelationships of these sleep breathing disorders with comorbid diseases and the received therapy in this cohort.Material and methods. 231 patients from a random sample were examined (men – 118 [51.1%], mean age 57.8±9.3 years) in the range of 1-6 months after catheter therapy for AF. All patients underwent cardiorespiratory sleep monitoring for one night. The criterion for OSA severity was apnea/hypopnea index (AHI) for hour (the norm is less than 5 events/h). Depending on the results obtained, all patients were divided into groups without apnea and with apnea of varying severity – a mild degree with an AHI value of 5 to 15 events/h, moderate severity with an AHI value of 16 to 30 events/h, and severe degree when the value of AHI more than 30 events/h. The study was performed without abolishing the basic therapy.Results. According to the results of cardiorespiratory sleep monitoring 127 patients (56.7%) with OSA criteria, were registered. Among them, a mild degree of OSA was found in 35.4% (n=45), a moderate degree – in 40.9% (n=52), and severe one – in 23.7% (n=30) of all patients with apnea. Among patients with obstructive sleep apnea 51.1% were males. Arterial hypertension was significantly more frequent in patients with OSA of pronounced degrees of severity compared with patients without apnea (p=0.047). Weight and body mass index of patients with OSA were significantly higher than in patients without apnea (p=0.001 and p=0.001, respectively). The left atrium (LA) size in patients with severe OSA was significantly larger than in patients without apnea (p=0.0005), which may indicate a possible contribution of severe obstructive apnea to the arrhythmia generating. OSA was the strongest independent factor among others related to the LA size (odds ratio was 1.6; 95% confidence interval 1.2-2.1; p<0.0003).Conclusion. Obstructive sleep apnea is very widespread among a cohort of patients with AF who have undergone a catheter procedure to isolate the pulmonary veins. Sleep breathing disorder is the strongest and most independent risk factor for AF associated with increased LA, among other risk factors such as age, hypertension, and obesity.